Reframing Food Insecurity in the Digital Era: Marginalized Women, Cultural Identity, and Public Policy Dynamics - Rarhore, Sonia (Yayasan Nurul Musthafa, 2025)
Food insecurity remains one of the most pressing challenges of the twenty-first century, disproportionately affecting women and marginalized communities. In recent years, digital technologies such as biometric identification, electronic vouchers, and online entitlement systems have been promoted as solutions to inefficiency and corruption in welfare distribution. However, these initiatives often reproduce existing inequalities, as women’s access to digital platforms is mediated by gendered, cultural, and socio-economic constraints. While existing scholarship has examined food insecurity, the digital divide, and intersectionality, these fields of study remain largely disconnected, leaving a gap in understanding how digital infrastructures themselves govern hunger. This paper addresses that gap by introducing the concept of the Digital Hunger Regime, a theoretical framework that explains how technological systems, bureaucratic rationalities, and cultural hierarchies interact to determine access to food. The study employs a conceptual methodology grounded in library research, critical discourse analysis, feminist theory, and decolonial critique, synthesizing policy documents, NGO reports, and scholarly literature to build a theoretical argument. The analysis demonstrates that digitalization in welfare is not a neutral tool of modernization, but a governance regime that often intensifies food insecurity while simultaneously creating limited spaces for resistance and alternative forms of solidarity. By reframing hunger in the digital era as a question of power, identity, and cultural justice, the paper contributes to debates in the humanities and social sciences, highlighting the hidden politics of digital welfare and offering a new lens for both academic inquiry and policy innovation. [Ketahanan pangan tetap menjadi salah satu tantangan paling mendesak di abad ke-21, yang secara tidak proporsional berdampak pada perempuan dan komunitas yang terpinggirkan. Dalam beberapa tahun terakhir, teknologi digital seperti identifikasi biometrik, voucher elektronik, dan sistem hak berbasis daring dipromosikan sebagai solusi untuk mengatasi inefisiensi dan korupsi dalam distribusi kesejahteraan. Namun, inisiatif-inisiatif ini sering kali mereproduksi ketidaksetaraan yang sudah ada, karena akses perempuan terhadap platform digital dimediasi oleh kendala gender, budaya, dan sosial-ekonomi. Sementara kajian yang ada telah meneliti ketahanan pangan, kesenjangan digital, dan interseksionalitas, bidang-bidang kajian tersebut sebagian besar masih terpisah, sehingga meninggalkan celah dalam memahami bagaimana infrastruktur digital itu sendiri mengatur persoalan kelaparan. Artikel ini menjawab celah tersebut dengan memperkenalkan konsep Digital Hunger Regime, sebuah kerangka teoretis yang menjelaskan bagaimana sistem teknologi, rasionalitas birokrasi, dan hierarki budaya berinteraksi dalam menentukan akses terhadap pangan. Studi ini menggunakan metodologi konseptual yang didasarkan pada penelitian kepustakaan, analisis wacana kritis, teori feminis, dan kritik dekolonial, dengan mensintesis dokumen kebijakan, laporan LSM, dan literatur akademik untuk membangun sebuah argumen teoretis. Analisis menunjukkan bahwa digitalisasi dalam program kesejahteraan bukanlah alat netral modernisasi, melainkan sebuah rezim tata kelola yang sering kali memperburuk kerawanan pangan sekaligus menciptakan ruang terbatas untuk perlawanan dan bentuk solidaritas alternatif. Dengan membingkai ulang kelaparan di era digital sebagai persoalan kekuasaan, identitas, dan keadilan kultural, artikel ini memberikan kontribusi pada perdebatan dalam ilmu humaniora dan ilmu sosial, menyoroti politik tersembunyi dari kesejahteraan digital serta menawarkan perspektif baru bagi kajian akademik maupun inovasi kebijakan.]